RSV vaccination uptake among adults aged 60 years and older in the United States during the 2023–2025 vaccination seasons - Elizabeth M. La; Catherine B. McGuiness; David Singer; Marie Yasuda; Chi-Chang Chen (Human Vaccines & Immunotherapeutics)
Older adults and adults with certain chronic conditions are at increased risk for severe respiratory syncytial virus (RSV) disease. In 2023, RSV vaccines first became available in the United States (US) for adults aged ≥60 years. This retrospective database analysis evaluated RSV vaccination uptake from August 2023–February 2025 using IQVIA’s open-source pharmacy (LRx) and medical (Dx) claims data. The study included US adults aged ≥60 years with ≥1 claim in 2023. For those without RSV vaccination in 2023, ≥1 claim was also required between January 2024–February 2025. Uptake was assessed as the number and percentage of eligible adults who received an RSV vaccine during the study period. Multivariable logistic regression modeling explored factors associated with RSV vaccination. Nearly 12.8 million adults aged ≥60 years (16.4%) received RSV vaccination between August 2023–February 2025. Uptake generally increased with age and was higher among those with ≥1 potential risk factor for severe RSV disease. Disparities in uptake were observed by race, ethnicity, and other social determinants of health. In multivariable analyses, odds of RSV vaccination were nearly 24 times higher for those who received ≥1 non-RSV vaccine from August 2023–February 2025 versus those who had not. Despite the increased risk of severe RSV disease among older adults and those with certain risk factors, relatively limited RSV vaccination uptake was observed during the 2023–2025 seasons, with disparities observed. Additional efforts are needed to support RSV prevention among those at highest risk and to ensure equitable access to vaccination.